GAMIFICATION IN THE TEACHING OF WORK SAFETY: A STRATEGY FOR THE TRAINING OF CIVIL ENGINEERS (Editora Impacto Científico, 2025)
Occupational safety is a fundamental field of engineering, particularly in civil construction, where accident rates remain high. Negligence regarding the use and monitoring of Personal Protective Equipment (PPE) compromises not only workers’ physical integrity but also productivity and occupational health at construction sites. In this context, the academic training of civil engineers must go beyond technical knowledge to foster an ethical and critical approach to prevention and compliance with regulatory standards, such as NR-6. Faced with the need for innovative teaching strategies, gamification emerges as a pedagogical alternative capable of making learning more interactive and effective. This study applied a quiz on safety standards and the use of PPE to 23 Civil Engineering students from a higher education institution in Maringá-PR, analyzing its effectiveness in reinforcing concepts and promoting a culture of safety. The results indicated that the ludic resource contributed to greater student engagement and enhanced knowledge retention, reinforcing the importance of integrating innovative practices into the teaching-learning process of occupational safety.